Tocotrienols rich fraction from palm oil (Elaeis guineesis Jacq.) as potential agent for diabetes. - Ting, Thing Min (2022)
Diabetic patients are exposing to high probability of chronic wound and increase risk of wound infection. Metformin is recognised as the standard drug for diabetes treatment to lower both basal and postprandial plasma glucose. Past research has reported that the treatment with metformin could accelerate wound healing besides regulating glucose level. However, overdose intake of metformin among patient with renal impairment may cause gastrointestinal discomforts, rare but high mortality rate in the case of lactic acidosis. This study aims to investigate a safe alternative to metformin to reduce its negative effects especially on diabetic subject. Tocotrienols Rich Fraction (TRF), a natural phytonutrient extracted from Elaeis guineensis (palm) oil has been researched and found to have many health benefits and potential medicinal effects. The potency of TRF extracted from palm oil in wound healing and diabetes management was investigated using Streptozotocin (STZ)-induced diabetes Sprague Dawley rat model. Two 6 mm full thickness excisions were created utilizing the sterile 6 mm punch biopsies on diabetic rats. A 400 mg/kg dosage of TRF per day was supplemented through oral gavage for 10 days. The wound closure rate, platelet derived growth factor-BB (PDGFBB) content, malondialdehyde (MDA) content, blood glucose level and body weight of the rats were monitored for a period of 10 days after wound creation. The results showed that TRF was comparable to metformin in stabilizing blood glucose, and stabilized the body weights of the diabetic rats suitable for diabetes use. TRF treatment as well as metformin treatment up-regulated the PDGF-BB in the blood on Day 2 of wound creation and 100% dry wound contraction at Day 10; indicated the non-delayed of growth factor at initial stage and total clean wound closure. TRF treated group detected significantly lower MDA content compared to metformin treated group. This shows TRF may have greater potency than metformin in reducing lipid peroxidation and promote better wound healing. Further analysis on the impact of TRF in modulating immune response in wound healing is recommended.